Enacting Space in Virtual Reality: A Comparison Between Money’s Road Map Test and Its Virtual Version - Morganti, Francesca (Frontiers in Psychology, 2018)
In the field of spatial cognition research the mutual relationship between perception and action that brings out spatial orientation was lately investigated. Besides, the sameness between creating a cognitive map from the exploration of a not simulated environment, from the use of an allocentric (survey-like) sketched map, and from the interaction with egocentric (route-like) 3D virtual environments, is generally contrived. To understand if different embodied affordances could provide different knowledge organization during wayfinding through the use of distinct spatial simulations, the same group of 61 healthy subjects experienced both the classical version of the Money’s Road Map test (M-RMT) and a virtual reality version of the Road Map test (VR-RMT). The M-RMT requires a allocentric to egocentric right/left reasoning to explore a stylized city provided in a survey perspective. The VR-RMT is a 3D version of the same environment through which participants can actively navigate by choosing egocentric-based right/left directions in a route perspective. The results showed that the different embodiments afforded by the two environments and the increasing complexity in turn types provides different spatial outcomes. Results were discussed according to the sensorimotor coupling theory provided from the enactive cognition approach and significances for spatial cognition research were provided.